Empowering Entrepreneurial Intentions: Educational Support And Self-Efficacy In MBKM Context - Lydiawati Soelaiman; Keni Keni; Ida Puspitowati (Jurnal Manajemen, 2024)
Realizing the importance of entrepreneurship for Indonesia’s development, the Indonesian government keeps increasing the entrepreneurship ratio. One is by launching the "Merdeka Belajar-Kampus Merdeka (MBKM)" policy to encourage the development of students' entrepreneurial intentions. This research aimed to empirically test the impact of MBKM-based entrepreneurial educational support on entrepreneurial self-efficacy and entrepreneurial intention through self-efficacy. Data was collected from 300 students of HEIs in Jakarta and Bandung. Data was processed by using PLS-SEM. The findings confirm that entrepreneurial educational support significantly and positively predicts entrepreneurial self-efficacy and intention. Moreover, the study validates that entrepreneurial self-efficacy mediates entrepreneurial educational support and intention. This research is expected to guide educators and policy-makers to understand better the factors that form the students' entrepreneurial intention, which can contribute to the growth of the Indonesian economy.